2023
DOI: 10.1088/1674-1056/accb8a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing high-energy x-ray and proton irradiation effects on electrical properties of P-GaN and N-GaN thin films

Abstract: The effects of ionizing and displacement irradiation of high-energy X-ray and 2 MeV proton on GaN thin films were investigated and compared in this study. The electrical properties of both P-GaN and N-GaN, separated from power devices, were gauged for fundamental analysis. It was found that the electrical properties of P-GaN were improved as a consequence of the disruption of the Mg-H bond induced by high-dose X-ray irradiation, as indicated by the Hall and circular transmission line model. Specifically, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Experiments and simulations indicated that doping superalloys with Re, Ru, Co, and W improved their mechanical properties. [18][19][20][21][22][23][24][25][26][27] Our previous work reported the lattice trapping limit increased for the Ni or Ni 3 Al cracks when Re or W was added and that W incorporation yielded much stronger effects for the Ni 3 Al cracks. [4,13,15] Other reports indicated the effect of Co on the crack propagation along the γ/γ interface was minimal.…”
Section: Introductionmentioning
confidence: 97%
“…Experiments and simulations indicated that doping superalloys with Re, Ru, Co, and W improved their mechanical properties. [18][19][20][21][22][23][24][25][26][27] Our previous work reported the lattice trapping limit increased for the Ni or Ni 3 Al cracks when Re or W was added and that W incorporation yielded much stronger effects for the Ni 3 Al cracks. [4,13,15] Other reports indicated the effect of Co on the crack propagation along the γ/γ interface was minimal.…”
Section: Introductionmentioning
confidence: 97%